Особливості планування і формування вимог для проєкту розробки медичної системи - Казимов, Л. Б. (ХНУРЕ, 2024)
This work analyzes approaches to planning and eliciting requirements for medical systems development projects, focusing on the use of major development models. It also highlights the steps for effective requirements elicitation, including stakeholder identification, research, user story development, and requirements prioritization. Applying these models allows teams to effectively plan and develop healthcare systems that meet stakeholder needs and project goals.
Keywords: медична система; розумний будинок